Rapid Biofilm Elimination on Bone Implants Using Near‐Infrared‐Activated Inorganic Semiconductor Heterostructures. Issue 19 (28th August 2019) - Hong, Li; Liu, Xiangmei; Tan, Lei; Cui, Zhenduo; Yang, Xianjin; Liang, Yanqin; Li, Zhaoyang; Zhu, Shengli; Zheng, Yufeng; Yeung, Kelvin Wai Kwok; Jing, Doudou; Zheng, Dong; et al.
Abstract: Bacterial infections often cause orthopedic surgery failures. It is hard for the immune system and antibiotics to clear bacteria adhered to implants after they form a mature biofilm, and a secondary surgery is required to remove the infected implants. To avoid this, a hybrid coating of Bi2 S3 @Ag3 PO4 /Ti is prepared to eliminate biofilm using near‐infrared (NIR) light. Bi2 S3 nanorod (NR) arrays are prepared on titanium (Ti) implants through hydrothermal methods, and Ag3 PO4 nanoparticles (NPs) are loaded on Bi2 S3 NR arrays using a stepwise electrostatic adsorption strategy. The introduction of Ag3 PO4 NPs enhances the photocatalysis performances of Bi2 S3, and the hybrid coating also exhibits good photothermal effects. After 808 nm light irradiation for 15 min, it shows superior bactericidal efficiency of 99.45% against Staphylococcus aureus, 99.74% against Escherichia coli in vitro, and 94.54% against S. aureus biofilm in vivo. Bi2 S3 @Ag3 PO4 /Ti also shows good cell viability compared to pure Ti. This NIR‐activated‐inorganic hybrid semiconductor heterojunction coating is biocompatible and could be employed to eliminate biofilm effectively, which makes it a very promising strategy for the surface modification of bone implant materials. Abstract : Bi2 S3 @Ag3 PO4 /Ti produces reactive oxygen species (ROS) and local heat under 808 nm near‐infrared irradiation. The hyperthermia increases bacteria cell membranes permeability and damages membrane protein. ROS penetrates into cell membranes and leads to bacterial metabolic disorders and protein leakage. Suffering from the synergy of photodynamic and photothermal therapy, the biofilm is broken.